Visualization study on the promotion of depressurization and water flow erosion for gas hydrate production. (February 2019) - Chen, Bingbing; Yang, Mingjun; Sun, Huiru; Wang, Dayong; Jiang, Lanlan; Song, Yongchen
Abstract: Natural gas hydrates (NGHs) are a potential energy source for the future. The efficient exploitation of NGHs has been a hot topic of worldwide research. At present, the depressurization is considered as the most effective method for NGHs exploitation. However, the lacking of hydrate decomposition driving force in depressurization anaphase and the ice generation phenomenon haven't been solved effectively. The combination method of depressurization with water flow erosion was carried out in this study. The experimental results indicated that driving force for MH decomposition will be not enough when the exploitation backpressure was higher than 2.4 MPa. The combination of depressurization with water flow erosion will efficiently solve the lacking of drive force for depressurization in anaphase and shorten the time of hydrate exploitation. The existence of chemical potential difference accelerated the hydrate decomposition.